62,7
Пошаговое объяснение:
66x5%=3,3
66-3,3=62,7
1) (-1 5/11+(-6 6/11))+(-3/7 + (-1 4/7))=-10
(-1 5/11+(-6 6/11)=-1 5/11-6 6/11=-8
-3/7 -1 4/7=-2
-8+(-2)=-8-2=-10
2) (-5 9/17+(-4 8/17))+(-4/15+(-4 14/15))=-15 1/5
-5 9/17+(-4 8/17)=-5 9/17-4 8/17=-10
-4/15+(-4 14/15)=-4/15-4 14/15=-5 1/5
-10+(-5 1/5)=-10-5 1/5=-15 1/5
3) (-1 2/7+(-3 5/7))+(-8 5/9)=-13 5/9
-1 2/7+(-3 5/7)=-1 2/7-3 5/7=-5
-5+(-8 5/9)=-5-8 5/9=-13 5/9
4) (-3 2/3) + (-1 4/9+(-6 5/9))=-11 2/3
-1 4/9+(-6 5/9)=-1 4/9-6 5/9=-8
-3 2/3+(-8)=-3 2/3-8=-11 2/3
Пошаговое объяснение:
1.7 tg x – 10ctg x + 9 = 0 | * tgx
7 tg²x -10 +9tgx = 0
tgx = z
7z² + 9z -10 = 0
z₁ = -2 z₂ = 5/7
tgx = -2 tgx = 5/7
x = arctg(-2) + πk , k ∈Z x = arctg(5/7 ) + πn , n ∈Z
2.0sinxcosx-14cos^2(x)+2sin^2x+2cos^x=0
2sin^2х+10sinxcosx-12cos^2x=0. (:соs^2x)
2tg^2x+10tgx-12=0 (:2)
tg^2x+5tgx-6=0
tgx=t
t^2+5t-6=0
D=49
t1=1
t2=-6
tgx=1
X=П/4+Пк;к€Z
tgx=-6
X=-arctg6+Пк;к€Z
3.9 cos 2x — 4 cos^2 x — 11 sin 2x — 9 = 0
9 cos^2 x — 9 sin^2 x — 4 cos^2 x — 22 sin x cos x = 0
2 cos^2 x + 9 sin^2 x + 11 sin x cos x = 0 | разделить на cos^2 x
2 + 9 tg^2 x + 11 tg x = 0
9y^2 + 11y + 2 = 0
(y + 1)(9y + 2) = 0
tg x = y; y1 = -1, y2 = -2/9
Пошаговое объяснение:
Пошаговое объяснение:
100% - 66 руб
пенсионеры заплятят 95% - x
x = 95*66/100 = 62.7